2010
DOI: 10.1002/he.410
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup dialogue and democratic practice in higher education

Abstract: Participants in intergroup dialogue examine the significance of social identities and social inequalities and practice intergroup communication and collaboration skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Intergroup dialog entails facilitating discussion between two groups on either side of a polarizing societal issue in a manner where all participants feel respected. The key to this approach is that it focuses on dialog and not debate (Dessel and Rogge, 2008); consequently this approach enables students to practice skills that they will need to create and nurture an inclusive culture both within and outside of higher education (Lopez and Zúñiga, 2010). Frantell et al (2019) found that using intergroup dialog produced several positive outcomes for participants; for example, ally development, perspective-taking, and critical consciousness.…”
Section: Dialogic Small Group Learningmentioning
confidence: 99%
“…Intergroup dialog entails facilitating discussion between two groups on either side of a polarizing societal issue in a manner where all participants feel respected. The key to this approach is that it focuses on dialog and not debate (Dessel and Rogge, 2008); consequently this approach enables students to practice skills that they will need to create and nurture an inclusive culture both within and outside of higher education (Lopez and Zúñiga, 2010). Frantell et al (2019) found that using intergroup dialog produced several positive outcomes for participants; for example, ally development, perspective-taking, and critical consciousness.…”
Section: Dialogic Small Group Learningmentioning
confidence: 99%
“…Scholars founded the first "formal" IGD program at the University of Michigan in 1989 as a response to racial tensions that occurred on campus between Black students and White students (Gurin et al, 2013;Moss et al, 2017;Zún ˜iga et al, 2007). Some higher education institutions offer curricular-based academic dialogue programs for academic credit in various disciplines such as sociology, psychology, communication, conflict resolution studies, social work, and education (Lopez & Zún ˜iga, 2010). Additionally, university offices outside of formal academic departments, such as diversity and inclusion centers or residential life offices, also offer cocurricular IGD programs.…”
Section: Igd In Higher Educationmentioning
confidence: 99%
“…Listening circles or town halls are one mode of fostering community dialogue among students (Lopez & Zúñiga, 2010). Listening circles, also known as restorative justice circles, peacemaking circles (Coates et al, 2003), or communal circles (Diaz Soto et al, 2009), derive from indigenous practices of community dialogue and are used in decolonial social justice praxis to hold people in positions of power accountable for maintaining systems of oppression, and to take collective action.…”
Section: Community Dialoguementioning
confidence: 99%